Effect of systemic oxygen as supplement therapy on corneal epithelial wound healing in diabetic patients after pars plana vitrectomy - Wee Min, Teh (2015)
Introduction: Diabetic patients are prone to developing corneal epithelial defects, either due to diabetic keratopathy or as a result of surgery such as pars plana vitrectomy. The healing time of corneal epithelial defects in this group of patients may also be delayed due to diabetes. Many substances have been investigated to determine their effects on corneal wound healing. Oxygen plays a key role as a nutrient for our tissues in the wound healing process. However, the effect of systemic oxygen on corneal epithelial wound healing is not known. Objective: To compare the corneal epithelial healing time between diabetic patients receiving and not receiving supplementary oxygen after vitrectomy; and to determine whether various factors such as age, duration of diabetes, duration of surgery, glycaemic control and haemoglobin level have any influence on corneal epithelial wound healing time. Methods: A randomised controlled trial was conducted involving diabetic patients planned for vitrectomy in Hospital Tuanku Ja’afar Seremban between October 2013 and October 2014. A 6mm circular corneal epithelial defect was created intra-operatively when there was obscuration of surgical field due to corneal haze. Post-operatively, these patients were randomised into two treatment groups; “Standard” (standard medical treatment of topical Maxitrol™ six-hourly and homatropine 2% six-hourly) or “Oxygen” (standard treatment plus systemic oxygen via simple face mask at 10 litres/min for one hour, in 12-hourly sessions for 3 days. Time taken for the corneal epithelial defect to heal completely was noted. Other parameters recorded were patients’ age, duration of diabetes, duration of surgery, recent HbA1C and haemoglobin level. Results: A total of 32 eyes of 32 patients were recruited in this study, consisting of 15 eyes in the standard treatment group and 17 eyes in the oxygen group. There were no significant differences between the two groups in terms of patient and disease demographics. The mean corneal epithelial wound healing time in the oxygen group was significantly faster than those in the standard treatment group (3.24 days vs 4.27 days, p = 0.040). Regression analysis showed no significant linear relationship between healing time and other factors such as age, duration of diabetes, duration of surgery, glycaemic control and haemoglobin level. Conclusion: Patients who received systemic oxygen therapy on top of the routine postoperative treatment for corneal epithelial defects after vitrectomy had a faster mean healing time. Oxygen administration may be considered in this group of patients to aid the wound healing process.